Daphne du Maurier - Kelly, Richard Michael, 1937- (Boston : Twayne Publishers, 1987)
A critical study of du Maurier's life and work including the films based on her work.
Includes index.
Bibliography: p. 150-151.
Wilson's Senior High School.
Young Adult.
Young Adult
Keywords: Du Maurier, Daphne, -- Dame, -- 1907-1989 -- Criticism and interpretation; Du Maurier, Daphne, -- Dame, -- 1907-1989 -- Criticism, interpretation, etc